Elucidating the Sole Contribution from Electromagnetic Near‐Fields in Plasmon‐Enhanced Cu2O Photocathodes. Issue 1 (5th November 2015) - DuChene, Joseph S.; Williams, Benjamin P.; Johnston‐Peck, Aaron C.; Qiu, Jingjing; Gomes, Mathieu; Amilhau, Maxime; Bejleri, Donald; Weng, Jiena; Su, Dong; Huo, Fengwei; Stach, Eric A.; Wei, Wei David
Abstract : Despite many promising reports of plasmon‐enhanced photocatalysis, the inability to identify the individual contributions from multiple enhancement mechanisms has delayed the development of general design rules for engineering efficient plasmonic photocatalysts. Herein, a plasmonic photocathode comprised of Au@SiO2 (core@shell) nanoparticles embedded within a Cu2 O nanowire network is constructed to exclusively examine the contribution from one such mechanism: electromagnetic near‐field enhancement. The influence of the local electromagnetic field intensity is correlated with the overall light‐harvesting efficiency of the device through variation of the SiO2 shell thickness (5–22 nm) to systematically tailor the distance between the plasmonic Au nanoparticles and the Cu2 O nanowires. A threefold increase in device photocurrent is achieved upon integrating the Au@SiO2 nanoparticles into the Cu2 O nanowire network, further enabling a 40% reduction in semiconductor film thickness while maintaining photocathode performance. Photoelectrochemical results are further correlated with photoluminescence studies and optical simulations to confirm that the near‐field enhancement is the sole mechanism responsible for increased light absorption in the plasmonic photocathode. Abstract : Cu2 O photocathodes are augmented with Au@SiO2 core–shell nanoparticles to exclusively evaluate the electromagnetic near‐field enhancement mechanism in a p‐type photocathode. Direct correlation between theory and experiment unambiguously demonstrates the sole influence of plasmonic near‐fields on the light‐harvesting efficiency of a semiconductor photoelectrode, and elucidates general design rules for the rational construction of plasmonic photocatalysts.